2015
DOI: 10.1007/s11515-015-1385-8
|View full text |Cite
|
Sign up to set email alerts
|

Smoothened regulation in response to Hedgehog stimulation

Abstract: The Hedgehog (Hh) signaling pathway play critical roles in embryonic development and adult tissue homeostasis. A critical step in Hh signal transduction is how Hh receptor Patched (Ptc) inhibits the atypical G protein-coupled receptor Smoothened (Smo) in the absence of Hh and how this inhibition is release by Hh stimulation. It is unlikely that Ptc inhibits Smo by direct interaction. Here we discuss how Hh regulates the phosphorylation and ubiquitination of Smo, leading to cell surface and ciliary accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 128 publications
0
9
0
Order By: Relevance
“…Although Ptch1 inhibits Smo while the pathway is inactive, the binding of the Hh ligand to Ptch1 causes phosphorylation of the Smo receptor, which results in localization of activated Smo onto cell surface, through inhibition of ubiquitination-mediated endocytosis and increased presence of its active conformation (Fig. 1C) (34, 35). Additionally, a required step in the transduction of the Hh pathway is the enrichment of the Smo receptor through intraflagellar transport to the primary cilium, a tightly controlled and activation-dependent event (3638).…”
Section: Introductionmentioning
confidence: 99%
“…Although Ptch1 inhibits Smo while the pathway is inactive, the binding of the Hh ligand to Ptch1 causes phosphorylation of the Smo receptor, which results in localization of activated Smo onto cell surface, through inhibition of ubiquitination-mediated endocytosis and increased presence of its active conformation (Fig. 1C) (34, 35). Additionally, a required step in the transduction of the Hh pathway is the enrichment of the Smo receptor through intraflagellar transport to the primary cilium, a tightly controlled and activation-dependent event (3638).…”
Section: Introductionmentioning
confidence: 99%
“…Smo acts as a signal transducer whose activity is inhibited by Ptc in the absence of Hh. How Ptc inhibits Smo is not completely understood, although recent studies indicate that phospholipids act in between Ptc and Smo in Drosophila Hh signaling 8 9 10 . Binding of Hh to Ptc alleviates Ptc-mediated inhibition of Smo, allowing Smo to activate Cubitus interuptus (Ci)/Gli transcription factors and ultimately induce the expression of Hh target genes, such as decapentaplegic (dpp ), patched (ptc) , and engrailed (en ) 11 12 .…”
mentioning
confidence: 99%
“…Studies have shown that Hh induces cell surface accumulation and phosphorylation of Smo by protein kinase A (PKA), casein kinase 1 (CK1), casein kinase 2 (CK2), and G protein-coupled receptor kinase 2 (Gprk2) (Chen and Jiang, 2013;Jiang and Jia, 2015), as well as atypical PKC (aPKC) (Jiang et al, 2014). Differential phosphorylation and gradual conformational change in Smo mediates the transduction of Hh activity gradient (Fan et al, 2012;Zhao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%